2008
DOI: 10.1021/jo801138s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tricyclic Phosphonopyrrolidines via IMDAF: Experimental and Theoretical Investigation of the Observed Stereoselectivity

Abstract: During the synthesis of tricyclic phosphonopyrrolidines via intramolecular Diels-Alder reactions of 1-acylamino(furan-2-yl)methyl phosphonates, two isomers are formed in most cases. The presence of a short three-atom tether together with spectroscopic data, including difference NOE, revealed that the cycloaddition occurred exo, but the phosphonate substituent on the tether had an exo or endo orientation. This was confirmed via X-ray analysis. A thermodynamic preference for the product with the phosphonate func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Amide C−N bond rotation has been investigated in a number of papers, and a rotational barrier in the range of about 6−100 kJ/mol was found, depending on the nature of the amide. The values found here fall within that experimental range. The activation energy for the rotation via TS1 is quite high, which can be ascribed to the lithium−halogen interaction.…”
Section: Resultssupporting
confidence: 74%
“…Amide C−N bond rotation has been investigated in a number of papers, and a rotational barrier in the range of about 6−100 kJ/mol was found, depending on the nature of the amide. The values found here fall within that experimental range. The activation energy for the rotation via TS1 is quite high, which can be ascribed to the lithium−halogen interaction.…”
Section: Resultssupporting
confidence: 74%
“…The structure of the tricyclic pyrrolidines was confirmed by its 2D DQFCOSY, HSQC and HMBC spectra and on comparison with literature data 21 and is clearly outlined in previous work. 6 The ring opening of 4¢ exo was first evaluated with Brønsted acids, such as p-toluene sulfonic acid, glacial acetic acid or HCl (aq) , which usually cause further aromatization; but either starting material was recovered or decomposition occurred with formation of complex reaction mixtures. Bases like NaOMe and LDA, are strong enough to deprotonate the a-position of the phosphonate resulting in the formation of a vinylic phosphonate by opening of the oxygen bridge towards a cyclohexenol derivative.…”
Section: Resultsmentioning
confidence: 99%
“…We earlier reported on the application of the intramolecular Diels-Alder reaction with furan (IMDAF reaction) in the synthesis of tricyclic phosphono pyrrolidines 4 (Scheme 1). 6 Intramolecular cycloaddition reactions such as the IMDAF reaction can achieve high levels of both regio-and stereoselectivity. 7 Only the exo-fused products were obtained and a combined experimental and modelling study showed that the position of the carbonyl group on the tether has an effect on the epimeric ratio of the phosphonate substituent on the pyrrolidine having an endo-or exo-position.…”
Section: Introductionmentioning
confidence: 99%
“…Claeys et al published a detail study of the kinetic exo and thermodynamic endo preferences in intramolecular Diels-Alder reactions of some phosphonate-derived furans (Scheme 26). 75 Norman et al published an interesting study of monodentate and bidentate ligand analogues aiming to elucidate differences in rate and enantioselectivity, exemplified in enantioselective hydrogenation reactions. 76 Canac et al also compared some ligand classes, concluding that phosphonium ylides are stronger donors than diaminocarbenes.…”
Section: Mechanistic Aspectsmentioning
confidence: 99%